Physical activity and coronavirus disease 2019 (COVID-19): specific recommendations for home-based physical training - Hammami, A.; Harrabi, B.; Mohr, M.; Krustrup, P. (Managing Sport and Leisure, 2022)
The novel coronavirus disease 2019 (COVID-19) seems to be having a major impact on physical activity behaviours globally. The pandemic has forced many people around the world to stay at home and self-isolate for a period of time. WHO recommends 60 min/day of moderate-to-vigorous physical activity for 6-17-yr-olds, and 75 min/wk of vigorous or 150 min/wk of moderate physical activity for adults and elderly, including 3 and 2 days/wk, respectively, with muscle and bone strengthening. Practical recommendations for staying active at home, with aerobic exercise training on a bike or rowing ergometer, bodyweight training, dance and active video gaming, can aid to counteract the detrimental physical and mental side-effects of the COVID-19 protective lifestyle regulations. This commentary provides useful information on home-based physical activity for sedentary people across the lifespan, including children and adolescence, that can be undertaken during the present pandemic or other outbreaks of infectious disease.